The Activities Of Combination Citrus hystrix Peel Extract and Carica papaya Leaves Extract Against Candida albicans and Escherichia coli : Aktivitas Campuran Ekstrak Kulit Citrus hystrix dan Ekstrak Daun Carica papaya Terhadap Candida albicans dan Escherichia coli - Anitasari, Septarini Dian; Sari, Dwi Nur Rikhma (Universitas Muhammadiyah Sidoarjo, 2021)
Citrus hystrix Peel Extract and Carica papaya Leaves Extract contain several active components that can be used as antimicrobial compounds. The aim was to test a mixture of extracts from Citrus hystrix peel and Carica papaya leaves as growth inhibiting compounds for Candida albicans and Escherichia coli. This study used 4 levels of treatment, namely a combination of papaya leaves extract and orange fruit peel at concentrations of 0%, 25%, 50%, 75% and 100%. The research data were in the form of the diameter of the growth inhibition of Escherichia coli and Candida fungi, which were analyzed using the Kruskall-Wallis test at 5% confidence level and 5% Duncan's test. showed a significant difference between treatments, but the concentration of 100% showed better results to inhibit Escherichia coli (1.58 ± 0.28 d) and the growth of Candida albicans (1.53 ± 0.57b) compared to controls and other concentrations.